Correlation between grain yield of pearl millet (Pennisetum glaucum L.) and soil quality indices under Sudan Savannah conditions - Abdullahi Aliyu, Nuraddeen; Ismail, Roslan; Mohammad Yusoff, Martini; Mohd Anuar, Mohd Firdaus; Naisa, Adamu Garba K. (Agri Bio Research Publishers, 2023)
For reasons of sustainable agriculture and land management, soil attributes have frequently been related to crop yields under various cropping systems. Grain yields of pearl millet and soil samples were collected from 36 plots at Kadawa and Dutsinma Research Farms for three consecutive wet seasons (2019, 2020 and 2021). The plots (under sole pearl millet cropping) were those that received full optimum fertilization (60 kg N/ha, 30 kg P2O5/ha and 30 kg K2O/ha plus 5 t/ha FYM) annually for at least four years. Grain yield and soil data were obtained according to standard procedures. Data analysis was performed using the Pearson product moment correlation of statistical analysis system (SAS) package, version 9.4. Results indicated that available phosphorus (AP), cation exchange capacity (CEC), soil fertility index (SFI) and soil evaluation factor (SEF) correlated positively and significantly with grain yield of pearl millet. While surprisingly, soil organic carbon (SOC) recorded a non-significant relationship with the grain yield. Therefore, it was suggested that AP, CEC, SFI and SEF were potential soil health indicators for appropriate management of Sudan Savanna Inceptisols.